Speech problem in cerebral palsy - Anantha Murthy HS (Journal of All India Institute of Speech and Hearing, 1972)
The Orthopaedic Centre of Andhra Mahila Sabha at Madras is treating childrensuffering from Cerebral Palsy. Being a Rehabilitation Unit it has a team of medicaland para-medical staff. At this Centre, a Cerebral Palsy Research and DemonstrationProject has been sponsored by the Department of Health, Eduction & Welfare,Social and Rehabilitation Service, Washington, U. S. A., to study the effect of stereotaxicsurgery in this condition. A speech therapy section was established in 1970 asa part of the Research Project. This paper analyses the speech problems that wereencountered in Cerebral Palsy